2019
DOI: 10.2196/13478
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Web-Based Interventions Delivered to Children and Young People With Neurodevelopmental Disorders: Systematic Review and Meta-Analysis

Abstract: BackgroundThe prevalence of certain neurodevelopmental disorders, specifically autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD), has been increasing over the last four decades. Nonpharmacological interventions are available that can improve outcomes and reduce associated symptoms such as anxiety, but these are often difficult to access. Children and young people are using the internet and digital technology at higher rates than any other demographic, but although Web-based int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 52 publications
1
32
0
6
Order By: Relevance
“…Sustainability of conventional anti-bullying interventions has also been limited so far, with rates of school participation decreasing over time (23). Digitally assisted interventions could help to address some of these limitations and decrease costs by reducing personnel effort and increasing the reach and homogeneity of interventions across settings (24), as previously suggested for other psychosocial or psychological therapies (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability of conventional anti-bullying interventions has also been limited so far, with rates of school participation decreasing over time (23). Digitally assisted interventions could help to address some of these limitations and decrease costs by reducing personnel effort and increasing the reach and homogeneity of interventions across settings (24), as previously suggested for other psychosocial or psychological therapies (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their affinity to technology, a promising development that may benefit CYP are online or digital health interventions (DHI). Randomized controlled trials (RCTs) have shown that DHIs can be effective in treating psychological and neurological symptoms for CYP [912] but they can also be ineffective [13, 14]. Hence, before any new DHI is introduced, clinicians, patients and commissioners need robust research to determine efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Com uma perspectiva mais ampla e em busca de estudos de alta qualidade metodológica, Khan et al (2019) realizaram uma revisão sobre a efetividade de intervenções baseadas em WEB para crianças e jovens com Transtornos do Neurodesenvolvimento. Os autores, incluíram somente estudos que realizaram experimentos controlados com amostra randomizada, considerado padrão ouro para práticas baseadas em evidências (Moher, Liberati, Tetzlaff, & Altman, 2009).…”
Section: Introductionunclassified